Solar Greenhouse Drying Kinetics Efficiency of Hydroxide Sludge in Marrakesh, Morocco - Fantasse, Azeddine; Idlimam, Ali; Khadir, Lakhal El; Bougayr, El Houssayne (Advanced engineering forum, 2024)
This paper presents a case study of solar drying of hydroxide sludge in the region of Marrakesh, Morocco. The experiments of solar greenhouse drying processes of the hydroxide sludge were studied in summer and winter seasons. The representative samples were in three volumes. The greenhouse sludge dryer was designed and constructed as a horticultural plant. Results showed that the dry of the three samples was reached in only 13 hours in summer and 25 hours in winter. The time of solar greenhouse drying registered was significantly lower compared to several studies. The higher values of drying rate were obtained in early hours of experiments in summer. The maximum ranges obtained were 0.25 kg water/kgDS.h for the hot season and 0.020 kg water/kgDS.h for the cold season. The important influence of the temperature had a greater effect with wind speed on drying rate. The sludge water evaporation caused a large volume reduction with a shrinkage during the processes in both seasons.